Optimal signal mapping scheme for MIMO-BICM-ID transmission over the different fading channel using whale algorithm - Nandal, Vikas; Kumar, Suresh (International Journal of Engineering and Technology, 2017)
The designing of signal mapping scheme for bit-interleaved coded modulation (BICM) systems has been received significant interest among the researchers recently due to the growing interest of using Multiple Input Multiple Output (MIMO) system. The bit-interleaved coded modulation systems are need of effective design in constellation mapping with iterative decoding that outperformed the existing BICM coding in time varying characteristics of the channel. In this paper, the design of optimal constellation mapping of the BICM system with iterative decoding for MIMO channel is proposed. Based on minimizing cost, a design criterion is proposed to find the optimal constellation mapping for an MIMO-BICM-ID system.Â Here, a cost function is designed to search an optimal mapping scheme using the well-known optimization algorithm called, whale algorithm.Â Using this method, we find some optimal constellation mapping for 2-dimensional and 3-dimensional cases. The designed technique is evaluated with the help of BER curve for different fading channels.Â